Kualitas Fisik dan Sensoris Produk Susu Pasteurisasi pada Suhu dan Waktu Transportasi dalam Distribusi Pemasaran (Faculty of Animal Science Universitas Brawijaya, 2018)
The aim of this research was to determine the influence of the long time transportation for 72 , 108 , and 129 hours at a temperature -15oC, 5oC , and 15oC. The materials used for this research wasÂ pasteurized milk packaging bottle 250 ml made in by UKM in Malang City. The study is conducted through simulate transportation with 9 treatment andÂ 3 replications. The treatment were 72, 108, and 129 h with temperature 15oC, 5oC , and -15oC. The variable observed were the pH, syneresis andÂ sensory (taste test , scent , texture and the bottle condition). Data analyzed by the descriptive analytic research. The pH values ranging from 4.6-6.7 and sineresis 55.03-93.88 %. Characteristic of pasteurized milk in the sensory (taste, aroma, texture and the bottle condition) tend to good condition, normal and bulging at a temperature of packaging 5 oC. Based on the normal milk of pH still in its approach is still normal sensory and properties, and marketing pasteurized milk can be done by long hours for the purpose of transportation 72-108 (location distribution Jember, Pekalongan, Yogyakarta, Sumenep, Denpasar, Mataram, dan Balikpapan) at a temperature of packaging 5 oC.